Assessment of the different citation systems in the scientific publication of nursing authors from Spanish-speaking countries - Joan De Pedro-Gómez; Miquel Bennasar-Veny; Francisco Guillem-Conejeros; Marcos Falque-Vidal; José Miguel Morales-Asencio (SciELO, 2021)
ABSTRACT Objective: To assess the distribution of citations of nursing authors in Spanish in Google Scholar as well as to compare the possible differences between this source and Web of Science and Scopus. Method: This is a descriptive cross-sectional study based on the citation systems offered by Google Scholar, Web of Science, and Scopus. Results: Nursing researchers present a verified mean h-index of 7.82 in Academic Google. 74% of researchers belong to the academic field, compared to 26%, who are in health services. Most of them live in Spain (83%), followed by Colombia (12%), Mexico (4%), and Chile (1%). In Spain, the community with the largest number of researchers is Andalusia (41.5%), followed by Valencia (14.6%), and Madrid (7.3%). Conclusion: The Google Scholar citation system requires adjustments in its algorithm for selecting works and citations, and it should also allow some system of confirmation by authors. Nursing can have relatively low h-index values compared to other courses due to short research development.